Japan’s Role in Africa - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, discussed how Japan’s success is an inspirational example for developing countries. Now, Japan is the second largest shareholder in the World Bank and a valued partner. Today the world is challenged to help the poor countries achieve the millennium development goals and that Japan and the World Bank have a common set of priorities in that endeavor. The Hong Kong round of the Doha development trade round is a big challenge ahead. The relationship between Japan and the World Bank is one of the most critical ones.